The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/0954406221997486
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory optimization for manipulators based on external archives self-searching multi-objective particle swarm optimization

Abstract: In order to improve the quality of the non-inferior solutions obtained by multi-objective particle swarm optimization (MOPSO), an improved algorithm called external archives self-searching multi-objective particle swarm optimization (EASS-MOPSO) was proposed and applied to a multi-objective trajectory optimization problem for manipulators. The position curves of joints were constructed by using quartic B-splines; the mathematical models of time, energy and jerk optimization objectives for manipulators were est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…In the unimproved GA algorithm combined with the BP algorithm, the fitness function used is the BP method, and the error is obtained by training in Eqs. (10)(11):…”
Section: Research On Cnc Lathe Performance Optimization Methods Based...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the unimproved GA algorithm combined with the BP algorithm, the fitness function used is the BP method, and the error is obtained by training in Eqs. (10)(11):…”
Section: Research On Cnc Lathe Performance Optimization Methods Based...mentioning
confidence: 99%
“…Experiments have shown that the particle swarm optimization algorithm, after improvement, has improved the ability of automatic optimization search. The method has better convergence and also reduces the time consumption [11]. Kumar et al [12] used fuzzy mathematics for model building and then used genetic algorithm for parameter optimization of this mathematical model.…”
Section: Introductionmentioning
confidence: 99%
“…The back-end trajectory optimization algorithm calculates a smooth trajectory with time parameters based on the front-end path. The back-end methods of the manipulator 30,31 can optimize a satisfied constrained trajectory, but the optimization process does not consider the obstacles. CHOMP algorithm 32 introduces the Euclidean Signed Distance Field (ESDF) information into motion planning to optimize trajectory using workspace gradient information.…”
Section: Motion Planningmentioning
confidence: 99%
“…After obtaining the front-end path, the back-end optimization methods must calculate a smooth trajectory containing time parameters. The trajectory optimization methods of the manipulator [15][16][17] can generate smooth trajectories. Still, these methods do not consider the influence of obstacles in the workspace and cannot guarantee the safety of the trajectories.…”
Section: Related Workmentioning
confidence: 99%